Disposition of [U-2H7]glucose into hepatic glycogen in rat and in seabass - Martins, Fátima O. (2013)
The stimulation of hepatic glycogenesis is a ubiquitous response to a glucose challenge and quantifying its contribution to glucose uptake informs its role in restoring euglycemia. Glycogenesis can be quantified with labeled water provided that exchange of glucose-6-phosphate hydrogen 2 (G6P-H2) and body water via glucose-6-phosphate isomerase, and exchange of positions 4, 5 and 6 hydrogens (G6P-H456) via transaldolase, are known. These exchanges were quantified in 24-h fasted rats (Rattus norvegicus; n=6) and 21-day fasted seabass (Dicentrarchus labrax; n = 8) by administration of a glucose load (2000 mg·kg−1) enriched with [U-2H7]glucose and by quantifying hepatic glycogen 2H-enrichments after 2 h (rats) and 48 h (seabass). Direct pathway contributions of the glucose load to glycogenesis were also estimated. G6P-H2 and body water exchange was 61 ± 1% for rat and 47 ± 3% for seabass. Transaldolase-mediated exchange of G6P-H456 was 5 ± 1% for rat and 10 ± 1% for seabass. Conversion of the glucose load to hepatic glycogen was significant in seabass (249 ± 54 mg·kg−1) but negligible in rats (12 ± 1 mg·kg−1). Preload plasma glucose levels were similar for seabass and rats (3.3 ± 0.7 and 4.4 ± 0.1 mmol·L−1, respectively) but post-load plasma glucose was significantly higher in seabass compared to rats (14.6 ± 1.8 versus 5.8 ± 0.3 mmol·L−1, p b 0.01). In conclusion, G6P-H2 and body water exchange is incomplete for both species and has to be accounted for in estimating hepatic glycogen synthesis and direct pathway activities with labeled water tracers. Transaldolase-mediated exchange is insignificant. Hepatic direct pathway glycogenesis plays a prominent role in seabass glucose load disposal, but a negligible role in the rat.